Peningkatan Kemampuan Bahasa Dengan Menggunakan Media Pembelajaran Berbasis Aplikasi Canva di RA Aisyiyah Bontorita Kab.Takalar (Sekolah Tinggi Agama Buddha Nalanda, 2023)
The problem in this study is How to Improve Language aspects by Using Canva Application-Based Learning Media at RA Aisyiyah Bontorita Kab. Takalar with this type of research is action research focused on classroom situations or commonly referred to as Classroom Action Research (Classroom Action Research) with the research objective of improving aspects of early childhood language by using canva application-based learning media at RA Aisyiya Bontorita Kab Takalar.The language skills of group B children at RA Aisyiyah Bontorita have increased as seen in the data, it can be seen that in cycle I there were 22 children who were in the criteria for starting to develop with a percentage of 100%. This is because there are still mistakes in each indicator so that in cycle I it is stated that it is not yet at the level of achieving success while in cycle II which is in the criteria for developing very well totaling 20 children with a percentage of 80% and which is included in the criteria for developing as expected 2 children with a percentage of 20% of each indicator of language ability after being given action by using Canva Application-based learning media. So it can be said that the research has improved learning outcomes, namely meeting the achievement of success or entering the Very Good Developing (BSB) category. Keywords: ,,